Pengembangan E-modul Menggunakan Aplikasi Ispring Suite 10 dengan Penguatan Literasi Numerasi Pada Peserta Didik SMP - Dzurrotul Hamiedah; Nur Fauziyah; Syaiful Huda (Universitas Muhammadiyah Gresik, 2023)
This research was conducted to produce an e-module product that was given numeracy literacy reinforcement using the Ispring suite 10 application for class VIII students of SMP/MTs. This study obtained 2 criteria valid and effective, so it deserves to be used as a reference for learning companions for students. The method used in this development research refers to the 4D model which consists of define, design, development, and disseminate. This development test was carried out on a limited basis because there was no time limit. To measure the validity of the e-module instrument used in this development research is an expert validation sheet, while to measure the effectiveness of the e-module instrument used is a response questionnaire, test instrument and student activity observation sheet. The results obtained in this development research are 1) Valid criteria which can be seen through the percentage of validation results by material experts with a percentage of 96.92% with an evaluation test of 95.56%, and media experts with a percentage of 91.25%. 2) Effective criteria which can be seen from the percentage of student activity is 78.33%, the percentage of classical completeness is 78.57% and the percentage of student responses is 88.6%. Thus, the development of e-modules using the Ispring suite 10 application by strengthening numeracy literacy can be used as a student learning companion.